Screening for gestational diabetes in women with class III obesity. (18th April 2012) - Scott, LJ; Mires, GJ; Long, G; Nicoll, AE
Abstract : Background: In Ninewells Hospital, Dundee all pregnant women are screened for gestational diabetes mellitus (GDM) by measuring random blood glucose (RBG) at 12 and 28 weeks gestation. It was felt that this might not be the most appropriate method for screening for GDM in women with class III obesity (First Trimester BMI >40kg/m2). Aims: To evaluate our current practice of screening for GDM in pregnant women with class III obesity and make recommendations for future practice. Methods: Retrospective review of all women (n=61) attending the metabolic antenatal clinic between 01/01/11-31/05/11. RBG was classed as abnormal if >7.0 mmol/L. Oral Glucose Tolerance Test (OGTT) was defined as abnormal if fasting blood glucose was >5.1 mmol/L and/or 2 hour blood glucose was >8.5 mmol/L. Results: All women had RBG at 12 and 28 weeks gestation. 25/61(41%) subsequently had OGTT. 11/61(18%) were diagnosed with GDM. 7/61(11%) had abnormal RBG and 5/7(71%) had abnormal OGTT. Of the remaining women with normal RBG18/54(33%) subsequently had OGTT. The indications for OGTT were glycosuria (n=3), large for gestational age (n=7), previous GDM (n=1), previous macrosomic baby (n=1) and not specified (n=6). 6/18(33%) had abnormal OGTT. Conclusions: A significant number of women with class III obesity will have OGTT irrespective of RBG result and a significant number of these women will be diagnosed with GDM. Our current screening method for GDM in women with class III obesity fails to identify GDM in at least 55% of cases. All pregnant women with class III obesity should have OGTT.